2023
DOI: 10.1088/1755-1315/1140/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tsunami disaster mitigation priority on urban area settlement

Abstract: Settlement in coastal areas is at risk of a tsunami disaster. In urban areas, the risk of disaster can be greater than the area behind it. This study aims to analyze the priority of tsunami disaster mitigation based on settlements criteria in urban areas. The data collection technique uses a questionnaire given to experts in the field of disaster mitigation. The research variables consisted of occupancy typology, settlement locations, settlement patterns and density, coastal environment, evacuation routes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The construction of breakwaters is one of the government’s efforts to protect coastal areas. According Soviana et al ( 2023 ), breakwater and/or embankment can reduce tsunami inundation level and protecting low-lying areas such as on the coast of Bnada Aceh City. In this case, the breakwater building is also used as a protection for the people on the coast when a tsunami disaster occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of breakwaters is one of the government’s efforts to protect coastal areas. According Soviana et al ( 2023 ), breakwater and/or embankment can reduce tsunami inundation level and protecting low-lying areas such as on the coast of Bnada Aceh City. In this case, the breakwater building is also used as a protection for the people on the coast when a tsunami disaster occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, evacuation routes also need to be developed to avoid crowding during the evacuation process by paying attention to several parameters such as pedestrian speed, available routes, route width and number of people who need to be evacuated (Koshimura et al 2006 & Wood et al 2016 ). A study conducted by Soviana et al ( 2023 ) in Banda Aceh City showed that the main road of Banda Aceh City consists of six lanes and two lanes, with lane widths capable of accommodating vehicles with a width of no more than 2.5 m. Secondary roads consist of two lanes and two lanes with road widths ranging from 4 m to 5 m.…”
Section: Preparednessmentioning
confidence: 99%